Effect of Plant Growth Regulators on Sprouting and Biomass Production of Tylophora asthmatica L. in Mid Hills of Himalaya - Chand, Gopi; Singh, R. D.; Meena, Ramjee Lal; Lal, Brij (Indian Forester, 2011)
The study was conducted to evaluate plant growth regulators (PGR) viz., IAA, IBA and NAA at three concentrations, 50, 100 and 200 mg/l, in terms of rate of sprouting in stem-cuttings and growth of the sprouted cuttings of Tylophora asthmatica, during July 2004 and 2006 in Palampur at mid hills of western Himalaya. Observations were recorded on sprouting rate, leaves per sprouted cutting, length of sprouted shoots and length of roots. Cuttings treated with IAA showed more than 50% sprouting, which was significantly higher than that due to other treatments and untreated control. Also, IAA was statistically superior to other PGRs in terms of growth of the sprouted cuttings. In terms of sprouting rate, the lowest rate of PGRs (50 mg/l) was more effective than the higher doses. In terms of biomass production, plant spacing of 50 Ã— 25 cm and 50 Ã— 50 cm were statistically comparable.